2020
DOI: 10.1155/2020/4039290
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic, Clinical, Ultrasonographic, and Cytological Features of Thyroid Nodules in Predicting Malignancy Risk: A Retrospective Study of 442 French Afro-Caribbean Patients

Abstract: Objective. To evaluate epidemiologic, clinical, cytological, and ultrasonographic features of thyroid nodules in a sample French Afro-Caribbean population to determine if the standard criteria for predicting malignancy risk are applicable to this specific ethnic population. Methods and Design. This retrospectively designed study consisted of 442 patients who had consulted with the Endocrinology Department in Martinique (French overseas department) between 2007 and 2011. Of the 442 patients, 641 ultrasound-guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 39 publications
11
14
1
Order By: Relevance
“…US findings, such as hypoechogenicity, increased blood flow, irregular margins, solid structure, microcalcification of the nodule and presence of abnormal cervical lymph nodes, which were identified as malignancy risk factors in our cohort, are in keeping with previous studies which have reported these characteristics to be more common in malignant nodules ( 38 , 39 , 40 , 41 ). Although hypoechogenicity and increased blood flow have high negative predictive value and high sensitivity, microcalcifications and presence of abnormal cervical lymph nodes have the highest specificity and positive predictive value and because of this, FNA is recommended for nodules with microcalcifications and abnormal lymph nodes, independent of nodule size ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…US findings, such as hypoechogenicity, increased blood flow, irregular margins, solid structure, microcalcification of the nodule and presence of abnormal cervical lymph nodes, which were identified as malignancy risk factors in our cohort, are in keeping with previous studies which have reported these characteristics to be more common in malignant nodules ( 38 , 39 , 40 , 41 ). Although hypoechogenicity and increased blood flow have high negative predictive value and high sensitivity, microcalcifications and presence of abnormal cervical lymph nodes have the highest specificity and positive predictive value and because of this, FNA is recommended for nodules with microcalcifications and abnormal lymph nodes, independent of nodule size ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…Problems in referrals that delay or hamper diagnosis and proper management of cases include insufficient information from the history and examination, incomplete laboratory and radiology tests, inappropriate FNAs, and even the experience of pathologists and cytologists in giving an accurate cytopathological diagnosis. 8 , 14 This paves the way for surgical and non-surgical management of benign cases indeterminate malignancy, and unnecessary surgeries will expose patients to surgical risks and complications. Molecular testing has become the current standard of care in most developed countries and has a huge advantage in reducing unnecessary thyroid surgeries and avoiding surgical complications, particularly in cases with indeterminate cytology results.…”
Section: Discussionmentioning
confidence: 99%
“…11 In 2015, the American Thyroid Association (ATA) published the updated clinical practice guidelines for the management of thyroid nodules; however, it was not clear on how this clinical practice guidelines differed from what doctors actually practice. [12][13][14] Several reports have noted that the 2015 guideline has a restricted approach to tissue sampling while others had distinguished its benefit in terms of quality, cost, and availability. 11,15,16 The management of thyroid nodules starts with a referral from a general practitioner to a family medicine practitioner, an internal medicine specialist, or an endocrinologist, and sometimes to an ear, nose, and throat (ENT) specialist or a general or endocrine surgeon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid nodule (TN) is a common thyroid disorder with global prevalence ranging; 4-7% by palpation, 19-68% by ultrasound, and 8-65% by pathologic examination at autopsy (1,2). This increase is thought to be related to early detection by high-resolution ultrasound and the discovery of subclinical TNs (3,4). TN can be classi ed as either benign or malignant.…”
Section: Introductionmentioning
confidence: 99%